2021
DOI: 10.1111/jcpt.13550
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, safety and cost‐effectiveness analysis of self‐administered outpatient parenteral antibiotic therapy via a disposable elastomeric continuous infusion pump at two county hospitals in Houston, Texas, United States

Abstract: What is known and objective Outpatient parenteral antibiotic therapy (OPAT) is an attractive option for patients who require parenteral antimicrobials as outpatients. Few OPAT studies have assessed the impact of IV antibiotic therapy via elastomeric continuous pumps, with most having been conducted outside the United States and few in county hospitals. The OPAT program in Harris Health system, the county hospital system of Houston, Texas, United States, has implemented a disposable elastomeric continuous infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Whilst no outcome data regarding cure or failure of treatment were reported by Cave et al, previous OPAT studies have found EMPs to be clinically effective. However, the authors note the low levels of evidence supporting this [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst no outcome data regarding cure or failure of treatment were reported by Cave et al, previous OPAT studies have found EMPs to be clinically effective. However, the authors note the low levels of evidence supporting this [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of EMPs for antibiotics is not new but is mainly confined to the outpatient setting, where studies have shown this method of administration to be safe and effective [ 8 , 9 ]. EMPs are included in the United Kingdom (UK) good practice guidelines for Out-patient Parenteral Antibiotic Therapy (OPAT) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, IV antibiotics were administered for the index cUTI episode, and patients were administered IV antibiotic therapy in a physician’s office or infusion suite. While OPAT is increasingly being used as a cost-efficient measure to facilitate early hospital discharge and minimize hospitalizations in otherwise healthy patients [ 40–42 ], the average 14-day OPAT costs exceeded $2500 across all cUTI study population subgroups. In addition to 14-day cUTI-related cost considerations with OPAT, data indicate that OPAT-related adverse events and subsequent hospital admissions/readmissions occur frequently [ 43–51 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 The use of self-administered elastomeric CI pumps for a total of 1925 OPAT days resulted in cost avoidance of $2.3 to $3.5 million relative to an inpatient-only treatment course. 6 A study in Spain among patients receiving CI OPAT via elastomeric devices (with piperacillin/tazobactam, 43%; meropenem, 20%; ceftazidime, 25%; ceftolozane/tazobactam, 3%; and cloxacillin, 2%) showed a similar cost avoidance of €745,290.55 associated with 1409 OPAT days compared with inpatient days. 7 Data are limited regarding cost comparisons among various OPAT delivery methods.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…26 More recently, penicillin was shown to be frequently prescribed and administered via elastomeric systems for neurosyphilis and other diseases, which resulted in substantial institutional cost savings. 6 Ampicillin, which has more limited stability than penicillin, has been less frequently used in elastomeric systems and may require the use of ambulatory electronic pump systems. Some stability data are available for ampicillin in an elastomeric device as well as in a plastic container (72 h refrigerated; 20 mg/mL concentration).…”
Section: Outcomes Associated With CI Antimicrobial Usementioning
confidence: 99%